Pengaruh Pemberian Rebusan Daun Pandan Wangi (Pandanus amaryllifolius Roxb) Terhadap Penurunan Glukosa Darah Pada Mencit (Mus musculus) - Brain Gantoro; Cevy Amelia; Nida Aqidatus Sholikhah (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2022)
Background :Diabetes mellitus (DM) is a degenerative disease caused by damage to the pancreas in production or insulin cannot work effectively. Boiled water of Fragrant Pandanus Leaf (Pandanus amaryllifolius Roxb) can help reduce blood glucose levels. The purpose of this study was to analyze the effect of boiled water fragrant pandanus leaf on blood glucose levels in male mice induced by glucose as a hiperglikemi model. Methods : 30 male mice were divided into 5 groups. Each group induced glucose 0.2ml/20gBB. The negative control group was given Na-CMC; the positive control group was given glibenclamide 0.01 ml/20gBW; treatment group 15% fragrant pandan leaf boiled water; treatment group 2 was given 10% fragrant pandan leaf boiled water; treatment group 3 boiled water of 20% fragrant pandan leaves. Examination of blood glucose levels was carried out after the intervention. Analysis of the results using the Kruskall Wallis test followed by Post Hoc Mann Whitney. Result : The results of Kruskal Wallis test on blood glucose level showed that had effect of giving the boiled water of Fragrant Pandanus Leaf in five groups treatment p=0,000. The result of Mann Whitney test showed that the boiled water of Fragrant Pandanus Leaf had effective antidiabetic activity at a dose of 20%. Conclusion : Based on the result of this study we can conclude the giving of boiled water fragrant pandanus leaf can reduce blood glucose levels.